Nutritional Assessment of Patients with Type-2 Diabetes in a Tertiary Level Hospital in a Low- and Middle-income Country - Subba, Rama; Luitel, Asmita; Joshi, Rinku; Baniya, Bhupal (Journal of Karnali Academy of Health Sciences, 2025)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by higher blood glucose levels. It is a global public health burden. One of the major risk factors for developing diabetes is inadequate dietary knowledge in many diabetic patients. This study was carried out to understand the dietary patterns of diabetic patients so that effective interventions can be taken for the proper management of a disease. Method: A cross-sectional study was conducted among a total of 266 patients with type 2 diabetes mellitus in a tertiary care hospital in Kathmandu, Nepal from 15 September to 15 December 2024. A purposive sampling technique was employed for the study. Descriptive statistics was used for the statistical analysis using SPSS version 23. Results: The majority of the respondents were male (54.14%) and 60 years and above in age (59.77%). Most of the patients were overweight and obese (BMI ≥25 kg/m2; 84.59%). The majority of the patients (65.41%) were taking medicines along with exercise and diet control, however, only 15.04% of patients were following the expert’s advice. 21.80% of the respondents were smokers and 19.55% were consuming alcohol even after diagnosis. More than one-fifth (22.55%) of the patients were consuming more calories than they needed. Conclusion: The study concluded that there was inadequate dietary awareness and compliance among the participants. The non-compliance may lead to complications of disease that significantly impact the healthcare system of the nation. Timely and careful interventions such as patient counseling and monitoring are necessary for the proper management of diabetes mellitus.